Dynamics of Marriage Age Limits in Indonesia: A Study of Psychology and Islamic Law - Yusuf Yusuf (Journal of Islamic Law)
Article 7 of Law No. 1 of 1974 established that the minimum age of marriage for men is 19 years old and women 16 years old. The regulation was amended through Law No. 16 of 2019 which sets the minimum threshold for marriage for men and women to be married is a minimum age of 19 years. Changes to the minimum marital boundaries are of course intended that the age of marriage becomes an inward part with the goal of marriage, animating the basis of marriage and it is hoped that in the future it will be able to minimize conflicts in the household. Unfortunately, the marriage age limit still causes dynamics. By using library research, there are three results of this study. First, Islamic law does not specify a minimum age for a bride and groom who will carry out the marriage. The foqoha’ differ in opinion in determining the age of maturity of a person in carrying out marriage but has the same goal, namely to establish goals rather than Islamic law. Second, psychologists think that the age of adulthood (adolescent) is right in carrying out marriage, that is someone who is 21 years old and so on. Third, the consequences of premature marriages will arise legal problems, biological problems, psychological problems, social problems, and problems of deviant sexual behavior.